PUBLIC SPEAKING TRAINING IN THE FRAMEWORK OF INCREASING JOURNALIST COMPETENCE IN SURABAYA - Rani Sukma Ayu Suteja; Santi Isnaini; Suko Widodo; Irfan Wahyudi; Dina Septiani; Andria Saptyasari; Nimas Safira Widhiasti Wibowo; Raniah (Jurnal Layanan Masyarakat, 2023)
Today's journalists are required to have good competence and broad insight.  Not only be able to write factual information, but also have a good public speaking skills.  However, there are still many journalists who do not master public speaking so they often face some obstacles.  They are proficient at finding information in the field, but are nervous or insecure when dealing with other people or sources, so the interviews become unstructured and directed.  A journalist is also often asked to be a speaker in a seminar, training, or workshop, but since they are not used to speak in public, the presentation of the material becomes less interesting.  In fact, journalism is a profession that is expected to be at the forefront of society who must be able to speak loudly, truthfully, honestly, and courageously.  Having good public speaking skills can increase the confidence of journalists in conveying information and ideas, as well as providing education and motivation.  Because public speaking is an important competency, the Communication Department held a community service activity entitled "Public Speaking Training in Increasing Journalist Competence in Surabaya" on 13th and 20th October 2022, at Urban Office Surabaya.  The training was attended by journalists who are members of the Friends of Education Journalists (JSP) community.